Perhitungan Harga Pokok Penjualan dan Peningkatan Laba Bagi Peserta UMKM Naik Kelas Kota Bogor - Mulyati, Sri; Azhar, Zul; Khim, Soei (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This community service activity aims to strengthen the understanding and skills of Micro, Small, and Medium Enterprises (MSMEs) in calculating Cost of Goods Sold (COGS) and developing strategies to increase business profits. This activity was held as part of the Closing Ceremony of the Bogor City MSME Naik Kelas Program, which serves as a final reinforcement for participants after participating in a series of MSME mentoring programs. The activity took place on Wednesday, January 21, 2026, in the Hall of Building B of the Kesatuan Bogor Business and Informatics Institute, and involved 50 MSMEs from various business sectors. The activity included material delivery, interactive discussions, and exercises and simulations on COGS calculations tailored to the characteristics of the participants' businesses. The results showed that participants gained an increased understanding of business cost components, COGS calculation techniques, and the relationship between COGS, selling price determination, and business profits. Furthermore, this activity encouraged changes in participant attitudes, particularly an increased awareness of maintaining more orderly financial records separate from personal finances. Overall, this community service activity made a positive contribution in supporting the process of upgrading MSMEs by strengthening their financial management. The closing ceremony is expected to provide MSMEs with the initial foundation for implementing sustainable cost management and profit planning